A Meta-Analysis of the Effects of Disclosing Sponsored Content. Issue 3 (26th May 2020) - Eisend, Martin; van Reijmersdal, Eva A.; Boerman, Sophie C.; Tarrahi, Farid
Abstract : The amount of literature on the effects of disclosing sponsored content has increased greatly in recent years. Although the literature provides valuable insights into the effects of disclosing sponsored content, several research gaps remain, such as inconclusive findings, boundary conditions, and the mechanisms that explain how disclosures work. This article offers a meta-analysis of 61 papers that use 57 distinct data sets to address these research gaps. The results showed that disclosing sponsored content reduced brand attitudes, credibility, and source evaluation but increased recognition, persuasion knowledge, and resistance. Disclosure content, timing, and awareness, as well as product and sample characteristics, provide boundary conditions for the positive and negative effects of disclosures. A path model that tested the mechanism of disclosing sponsored content showed that, as suggested by memory priming effect, recognition of sponsored content increased memory but did not influence evaluation. Moreover, the understanding of sponsored content influenced evaluation, but memory remained unaffected, which corresponds to the flexible correction approach (i.e., consumers try to correct their answer to limit persuasive effects).